2021
DOI: 10.3389/fevo.2021.703208
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Avian Egg Traits Cueing Egg-Rejection Defenses Against Brood Parasitism

Abstract: The capability of hosts to reject the odd egg from their nest is one of the key defenses against avian brood parasitism. Considerable research effort has been devoted to exploring which phenotypic traits of eggshells facilitate to cue the recognition of the parasitic egg. Here we have reviewed studies addressing salient egg traits involved in the rejection of foreign eggs and used a formal meta-analysis to quantify their relative importance. Hosts appear to rely to a large extent on eggshell color traits, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…In a recent and large‐scale meta‐analysis conducted across all hosts and brood parasites (Samaš et al, 2021), eggshell color was the most frequently investigated trait in obligate brood parasitism experiments. Since model cuckoo eggs painted to be mimetic or nonmimetic to blackbird eggs were frequently used in experimenting with Eurasian blackbird populations, and blackbird eggs are larger than cuckoo eggs (Moskát et al, 2003), many of the tests in blackbirds tested both color and size (see below, 3.1.1.3).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent and large‐scale meta‐analysis conducted across all hosts and brood parasites (Samaš et al, 2021), eggshell color was the most frequently investigated trait in obligate brood parasitism experiments. Since model cuckoo eggs painted to be mimetic or nonmimetic to blackbird eggs were frequently used in experimenting with Eurasian blackbird populations, and blackbird eggs are larger than cuckoo eggs (Moskát et al, 2003), many of the tests in blackbirds tested both color and size (see below, 3.1.1.3).…”
Section: Resultsmentioning
confidence: 99%
“…Once laid, eggs are typically protected and incubated in nests until they successfully hatch. There are three major exceptions to this pattern: (i) the rejection of brood-parasitic eggs from the nests of many host species [ 1 3 ], (ii) the pecking and destruction or the removal of eggs by some brood parasites in hosts' nests [ 4 , 5 ], and (iii) the predation and consumption of eggs ([ 6 ]; not the subject of this study).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Honza et al (2014) found that cuckoos from this population selectively targeted hosts that laid eggs perceptually similar to their own. Studies such as this provide a powerful dataset to test hypotheses that depend on the egg phenotypes of both hosts and parasites, and how co-evolutionary dynamics may be shaping the evolutionary trajectories of both parties [23]. Due to prior work finding color-biased egg rejection in this species [15], we predict that hosts selection for bluer cuckoo eggs would result in reciprocal negative frequency-dependence, such that hosts should have bluer eggs than their parasite.…”
Section: Introductionmentioning
confidence: 99%